The Ability to Understand Questions of Writing Scientific Works based on Higher Order Thinking Skill (HOTS) in SMAN 3 Medan - Eko Firman Susilo; Abdurrahman Adisaputera; Malan Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study discusses about the ability to understand questions of writing scientific based on higher order thingking skill (HOTS) in SMAN 3 Medan. This type of research uses research and development in the field of education known as Research and Development (R & D). The location of this research is at SMAN 3 Medan. The research is conducted in the 2018/2019 Learning Year. The subjects in this study are 30 students  of Class X of SMAN 3 Medan. The result shows that the ability to understand the assessment instrument questions of writing scientific work based on higher order thinking, students get an average value of 71 with sufficient categories.